Aplikasi Pengolahan Data Santri Berbasis Desktop Menggunakan Visual Studio 2012 - Tarsinah Sumarni; Sulis Setiawati (FKOM UNIKU, 2022)
In its activities of managing student data, exit permit data and student discipline violations, Ruqu Madani has not implemented a computerized system. In addition, data transparency has not been fulfilled properly because the old system did not yet have a form of reporting exit permit activities and student discipline violations to the head of the foundation. The author conducts research by designing a system using an application that is able to produce computerized data storage and reports both in print and in soft files. It is hoped that by using this system the existing problems can be resolved and the chairman of the foundation can read more clearly the data on the behavior and attitudes of his sons and daughters while in the pesantren. This study aims to: (1) design and develop a desktop-based student data processing information system that suits the needs of Ruqu Madani (2) to determine the quality of the information system developed based on the knowledge that has been obtained during lectures. The method used in this research is the research and development (RD) method. Keywords: Santri data processing, Exit permission, Microsoft Visual Studio, Ruqu Madani Information Management System, RD.